2016
DOI: 10.1039/c6ra02992b
|View full text |Cite
|
Sign up to set email alerts
|

Structure and bonding of IrB12: converting a rigid boron B12 platelet to a Wankel motor

Abstract: DFT‐based calculations reveal that the global minimum of IrB12‐ is a C3v symmetric bowl‐like structure in which the Ir atom is located on the concave side of the bowl similar to its lighter congeners, CoB12‐ and RhB12‐.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 29 publications
4
53
0
Order By: Relevance
“…In this paper, we examined the result of substituting two or three C atoms into small B 16 and B 19 clusters. Using extensive computation, 20,000 possible configurations were examined in a comprehensive search for the ground state and low-level excited states of C 2 B 14 − and C 3 B 16 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this paper, we examined the result of substituting two or three C atoms into small B 16 and B 19 clusters. Using extensive computation, 20,000 possible configurations were examined in a comprehensive search for the ground state and low-level excited states of C 2 B 14 − and C 3 B 16 .…”
Section: Discussionmentioning
confidence: 99%
“…They found a planar structure, and theoretical calculations showed that the global minimum of B 19 − is a nearly circular planar structure with a central B 6 pentagonal unit bonded to an outer B 13 ring [2]. They also studied B 16 2− with 10 π-electrons, which is an interesting all-boron analogue of naphthalene [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 The combination of a PBE0 functional with a def2-TZVP basis set has been widely used to study the electronic structures of boron clusters. 11,17,24 The bonding interactions corresponding to the formation of close-and open-B12X7 − have been analyzed with the EDA scheme. 25 These calculations were performed at PBE0 level with the basis set of TZ2P.…”
Section: Computational Detailsmentioning
confidence: 99%